From Network Security to Network Autonomous - Wang, Yubian; Yuri, Shebzukhov (International journal of advanced network, monitoring, and controls, 2019)
In the 20th century, the emergence of the Internet has completely changed the work and life of human beings around the world. Today, people are increasingly inseparable from network. The Internet has been integrated with the global industry, agriculture, education, science, technology and national defense. The current Internet was originated in the United States. The Internet systems based on IPv4 and IPv6, they are controlled by the United States completely. Computers connected to the Internet are subject to data retention and backup in the United States. Data security is greatly threatened. In addition, due to limitations and loopholes in the design of the Internet, the Internet is subject to many different types of attacks. Internet research which based on security autonomy has received the attention of sovereign countries in the world. This paper mainly introduces the Future Internet system developed by Chinese researchers based on the current research on Internet servers, which is a new generation network system, the research and application of this system will have a profound impact on the world’s Internet.